Data from: Experimental warming increases herbivory by leaf-chewing insects in an alpine plant community - Birkemoe, Tone; Bergmann, Saskia; Hasle, Toril E.; Klanderud, Kari (Dryad Digital Repository, 2016)
Climate warming is predicted to affect species and trophic interactions worldwide, and alpine ecosystems are expected to be especially sensitive to changes. In this study, we used two ongoing climate warming (open-top chambers) experiments at Finse, southern Norway, to examine whether warming had an effect on herbivory by leaf-chewing insects in an alpine Dryas heath community. We recorded feeding marks on the most common vascular plant species in warmed and control plots at two experimental sites at different elevations and carried out a brief inventory of insect herbivores. Experimental warming increased herbivory on Dryas octopetala and Bistorta vivipara. Dryas octopetala also experienced increased herbivory at the lower and warmer site, indicating an overall positive effect of warming, whereas B. vivipara experienced an increased herbivory at the colder and higher site indicating a mixed effect of warming. The Lepidoptera Zygaena exulans and Sympistis nigrita were the two most common leaf-chewing insects in the Dryas heath. Based on the observed patterns of herbivory, the insects life cycles and feeding preferences, we argue that Z. exulans is the most important herbivore on B. vivipara, and S. nigrita the most important herbivore on D. octopetala. We conclude that if the degree of insect herbivory increases in a warmer world, as suggested by this study and others, complex interactions between plants, insects, and site-specific conditions make it hard to predict overall effects on plant communities. Feedingmarks on Dryas octopetala and Bistorta vivipara inside and otside OTCs at Finse, NorwayThe data is based on field observations in two summer periods. The file consists of 3 datasheets: 1. used in table 1 in publication with feeding marks on Bistorta and Dryas. Feeding index as defined in publications 2. feeding marks on other common plant species 3. precentage of each leaf removed (table 2 in publication).HerbivoryFinse.xlsx